Movie Therapy To Developing Prosocial Behavior of Childhoods - Dian Renata; Hengki Satrianta; Rezky Permatasari; Anna Rufaidah; Sri Utami; Afiatin Nisa (Program Studi Pendidikan Agama Islam (PAI) Sekolah Tinggi Agama Islam Al Azhar, 2020)
Movie Therapy To Developing Prosocial Behavior Of Childhoods. The phase of human life was beginning from the prenatal period and will end in late adulthood. Childhoods is critical age or golden age. In this phase childs tend to be selfish and far form prosocial behavior. This was need to be given intervention. One of intervention than can given through movie therapy. This article aim to describe whether movie therapy can develop prosocial behavior of childhoods. This research used quantitative research with experiment method. Samples in this research was 17 students. Instrument of this research was used prosocial behavior scale. Data were analyzed by sign test. The result shown that movie therapy was able to develop childhoods prosocial behavior. Implications of this findings in teacher and especially school counselors must to try this method to help childhoods with the lack of prosocial behavior. So, happy watching!